Narrativas de professores no ensino tecnológico - Campos, Alessandra Tomé (2015)
This work is the result of research done in the Professional Master in Technological Education (MPET) at the Federal Institute of Education, Science and Technology (IFAMCampus Center) with the main question understanding teachers narratives in training, student and researcher in said master to obtain indicators, to be used as reference for the preparation of a resource, it can be used in training teachers process of Technological Education. Aiming to reach that goal, at first, we tried to establish a parallel between the of the researcher's life story, his experiences in the first year of MPET with the theoretical and epistemological foundations on Narrative Research subsidized by theorists like Clandinin and Connelly (2011), Ricoeur (2010), among others. Secondly, there was Discursive Textual Analysis (ATD), using as theoretical support and Galiazzi, Moraes (2011) and for an analysis of equipment, the narratives of life of teachers in training the first group of master's. As methods and techniques have been used bibliographical research works concerning the Narrative Research, teacher training and Technological Education, held natural participant observation that was adequate to the proposed objective since the researcher is part of the group of teachers, subjects research. Data collection was conducted from moments of observation of classes held in the first year of training in the MPET, the II Conference and Project Seminar from which were made field notes of descriptive and reflective type, records through photographs, sound recordings and image of said time of observation. Based on indicators emerging from this process ATD, it showed the potential of narratives in contributing to teacher training, and from there, we proceeded to the preparation of the site / blog Narratives on MPET (www.narrativasnomept.com) as a possible resource to contribute in formation process of teachers who work in Technological Education. Finally, it is expected that with the use of this resource through the development of the proposed topics and from the interaction activities, arising referrals for future research.